A synthesis of the basal thermal state of the Greenland Ice Sheet. Issue 7 (23rd July 2016) - MacGregor, Joseph A.; Fahnestock, Mark A.; Catania, Ginny A.; Aschwanden, Andy; Clow, Gary D.; Colgan, William T.; Gogineni, S. Prasad; Morlighem, Mathieu; Nowicki, Sophie M. J.; Paden, John D.; Price, Stephen F.; Seroussi, Hélène
Abstract: The basal thermal state of an ice sheet (frozen or thawed) is an important control upon its evolution, dynamics, and response to external forcings. However, this state can only be observed directly at sparse boreholes or inferred conclusively from the presence of subglacial lakes. Here we synthesize spatially extensive inferences of the basal thermal state of the Greenland Ice Sheet to better constrain this state. Existing inferences include outputs from the eight thermomechanical ice‐flow models included in the Sea Level Response to Ice Sheet Evolution (SeaRISE) effort. New remote‐sensing inferences of the basal thermal state are derived from Holocene radiostratigraphy, modern surface velocity, and Moderate Resolution Imaging Spectroradiometer (MODIS) imagery. Both thermomechanical modeling and remote inferences generally agree that the Northeast Greenland Ice Stream and large portions of the southwestern ice‐drainage systems are thawed at the bed, whereas the bed beneath the central ice divides, particularly their west facing slopes, is frozen. Elsewhere, there is poorer agreement regarding the basal thermal state. Both models and remote inferences rarely represent the borehole‐observed basal thermal state accurately near NorthGRIP and DYE‐3. This synthesis identifies a large portion of the Greenland Ice Sheet (about one third by area), where additional observations would most improve knowledge of its overall basal thermal state. Key Points: The bed is likely thawed under Greenland's southwestern and northeastern ice drainages The bed is likely frozen in Greenland's interior, west of the ice sheet's central ice divide The basal thermal state of a third of the Greenland Ice Sheet is poorly constrained